An observational study on the surgical antibiotic prophylaxis in the surgery ward of a tertiary care hospital - Kudchadkar, Aditi A.; Bhounsule, Sushama A. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Surgical site infection (SSI) is the most common postoperative complication and represents a significant burden in terms of patient morbidity, mortality and cost to health services around the world. Appropriate antibiotic prophylaxis helps in reducing the incidence of SSIs. Appropriate surgical prophylaxis is a multifactorial process that depends on proper case selection, antibiotic selection including dosing and route of administration and duration of therapy. Methods: A prospective observational study was conducted over 3 months on 200 operated patients in surgery ward of a tertiary hospital. Patient details like demography, type of surgery performed and antibiotics prescribed pre and post-surgical procedure was collected and analysed using Microsoft excel. Results: Out of 200 patients 32.5% (65) were females and 67.5% (135) were males. Total number of prophylactic antibiotics prescribed were 368. The most commonly prescribed group of antibiotics was cephalosporins (44.29%) followed by metronidazole (26.5%) and ofloxacin (9.48%). Among the cephalosporins the most commonly prescribed was cefuroxime in 82 patients (50.3%) and cefoperazone in 79 patients (48.46%). SSI developed in 3 out of 200 patients (1.5%). Conclusions: There is an urgent requirement to promote rational antibiotic prescribing among surgeons. The need of the hour is developing and implementing national guidelines for surgical prophylaxis by a multidisciplinary group of experts.